2020
DOI: 10.3934/microbiol.2020017
|View full text |Cite
|
Sign up to set email alerts
|

<em>Candida africana</em> and <em>Candida dubliniensis</em> as causes of pediatric candiduria: A study using <em>HWP1</em> gene size polymorphism

Abstract: Background Candida species cause a wide spectrum of disease entities. Candida africana and Candida dubliniensis –members of Candida albicans complex-are currently gaining both clinical and epidemiologic significance. Materials and methods Totally, 150 pediatric isolates that had previously been identified as C. albicans species complex based on a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…C. albicans , C. dubliniensis , and C. africana [ 7 ]. In the present study, C. albicans (94.89%) was the predominant species among the 235 isolates, which is in line with the results of some previous studies [ 12 , 16 , 21 - 24 ]. In the present research, the majority (97.3 %) of C. albicans with 941 bp DNA fragments were homozygous, while 2.97% (n=7) of them produced two DNA fragments of 850 and 941 bp, demonstrating heterozygosity at HWP1 locus.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…C. albicans , C. dubliniensis , and C. africana [ 7 ]. In the present study, C. albicans (94.89%) was the predominant species among the 235 isolates, which is in line with the results of some previous studies [ 12 , 16 , 21 - 24 ]. In the present research, the majority (97.3 %) of C. albicans with 941 bp DNA fragments were homozygous, while 2.97% (n=7) of them produced two DNA fragments of 850 and 941 bp, demonstrating heterozygosity at HWP1 locus.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, C. africana (3.4%) had a higher prevalence rate than C. dubliniensis (1.7%). This result corroborates those of the previous research performed in Iran [ 7 , 12 , 26 - 28 ]. However, the higher isolation rate of C. dubliniensis over C. africana has also been reported in other studies [ 21 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These culture media have the same limitation as corn meal agar and could not differentiate C. dubliniensis and C. africana from C. albicans 47–49 . Similarly, although germ tube test can discriminate between C. albicans and NAC species, it has similar results for C. albicans , C. dubliniensis , and C. africana 49,50 . As a solution for these limitations, molecular techniques have been used as complement to conventional methods that provide accurate outputs in a short time (1.5–3 h) 51 .…”
Section: Diagnosismentioning
confidence: 99%
“…Recent studies have shown that most of vaginal C africana isolates from Iran exhibit resistance to various antifungal drugs, 21,22 and ~28% of world isolates appear to be resistant to itraconazole 23 . Furthermore, although C africana is generally associated with vaginal infections, in Iran, this pathogen has also been reported as a cause of paediatric candiduria, 24 and/or oropharyngeal candidiasis in cancer patients 25 . From these latter patients, fluconazole‐ and amphotericin B‐resistant isolates have been also recovered 25 .…”
Section: Introductionmentioning
confidence: 99%